Pembuatan Kroket Berbahan Dasar Ubi Jalar (Ipomoea Batatas) dengan Isian Sayur dan Daging Ayam - Khairani, Miftahul; Roji, Fadilla; Hernita, Friska; Siregar, Sa’adatun Nizwah; Lubis, Sumayyah Assa’adah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Croquettes are a spicy appetizer and a kind of continental dish made from carbohydrates and animal protein, with the addition of vegetables. This dedication is carried out in Sampali Village, Deli Serdang Regency. The aim is to raise awareness or empower the community through training seminars that utilize sweet potatoes as a staple ingredient to replace potatoes in making croquettes. The stages of implementing this dedication include observation, planning, action, and evaluation. The method used is the PAR (Participatory Action Research) method with the aim of building community awareness or empowering the community through critical education by dialogue, public discussion, and adult learning. The results of this activity include increased knowledge of students and the community with the innovation of students in making croquettes from sweet potatoes filled with meat and vegetables, making it a potential business for students and the community. The selling price of sweet potato croquettes is 5000/3pcs.